2013
DOI: 10.5812/nms.13316
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Evaluation of Their Use and Mastery in Health Assessment Skills: Selected Iran's Hospitals

Abstract: Background: Health assessment skills are of the most important skills which nurses require. The more precise assessment, the better results would be obtained and the quality of patient care would be improved. However, in Iran, few studies have investigated nurses' assessment skills. Objectives: This study was aimed to assess nurses' evaluation of the learned skills of health assessment and their use. Materials and Methods:This cross-sectional study was conducted on 200 nurses in Isfahan province hospitals. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Modifying the curriculum and cooperating of nurse managers and nursing schools can help to improve the situation. 5 The above findings also supported by a study carried out by Giddens JF in 2007. A survey of physical assessment of techniques performed by RNs: lessons for nursing education.…”
Section: Discussionsupporting
confidence: 73%
“…Modifying the curriculum and cooperating of nurse managers and nursing schools can help to improve the situation. 5 The above findings also supported by a study carried out by Giddens JF in 2007. A survey of physical assessment of techniques performed by RNs: lessons for nursing education.…”
Section: Discussionsupporting
confidence: 73%
“…Self-assessment can also empower staff and help them to pick higher professional goals and to try harder to realize these goals. 24,25…”
Section: Introductionmentioning
confidence: 99%
“…This is somewhat consistent with a previous study by Sorensen, where assessment and care planning were introduced as the main indicators of healthcare system accreditation ( 3 ). However, Adib-Hajbaghery and Safa investigated nurses’ evaluation of their use and mastery of health assessment skills and reported that nurses use these skills below the desired level ( 14 ). Nurses’ adherence to the nursing process differs across settings.…”
Section: Discussionmentioning
confidence: 99%